2003
DOI: 10.1542/peds.112.5.1127
|View full text |Cite
|
Sign up to set email alerts
|

Intervention With Parental Smokers in an Outpatient Pediatric Clinic Using Counseling and Nicotine Replacement

Abstract: This study demonstrates the feasibility of engaging parents in a smoking cessation intervention at the time of a child's clinic visit. This approach may be an effective way to reach smokers who otherwise are unlikely to access smoking cessation interventions. High rates of program enrollment, use of NRT, and completion of telephone counseling in this study support the hypothesis that a child's clinic visit is a teachable moment to address parental smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 53 publications
4
76
0
Order By: Relevance
“…Questions used in this study to assess tobacco control service delivery were used previously in our other inpatient or outpatient studies. 16,22 Covariates collected included gender, age, race, education, smoking history, smoking behavior inside the home and car, and attitudes about the dangers of child' s TSE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Questions used in this study to assess tobacco control service delivery were used previously in our other inpatient or outpatient studies. 16,22 Covariates collected included gender, age, race, education, smoking history, smoking behavior inside the home and car, and attitudes about the dangers of child' s TSE.…”
Section: Methodsmentioning
confidence: 99%
“…11,16,21,22,[29][30][31][32] The intervention includes (1) routine screening for parental tobacco use using a CEASE Action Sheet, which helped the office staff identify each smoking family member and document smoking status in the child' s medical record; (2) motivational messaging that is based on the parents' own concerns as well as potential teachable moments that may be cued by the child' s illness; and (3) recommendation and possible provision of nicotine patch and gum by the clinician, and enrollment in the free state quitline. The intervention is designed to function within existing systems of care; research staff deliver none of the clinical tobacco dependence treatment.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The majority of parents who smoke would accept quitline enrollment in the context of their child's visit to the doctor. 27,28 Previous qualitative work suggested that fathers were not likely to rely on smoking cessation resources to help them quit. 29 High rates of quitline enrollment and counseling in our study suggest that low rates of fathers' previous use of smoking cessation resources may reflect poor access rather than unwillingness to use available resources.…”
Section: Figurementioning
confidence: 99%
“…77 Also encouraging is the finding that, in another study, more than one half of smoking parents tried to quit after being counseled at their children's clinic and offered nicotine replacement therapy and quit-line referrals. 78 The tobacco industry's disinformation campaign regarding SHS and maternal and child health can be counteracted within clinicians' offices. SHS must be recognized as an established, controllable, risk factor for SIDS, like prone sleep positioning.…”
Section: Discussionmentioning
confidence: 99%